A Comprehensive Assessment of the Person–Environment Fit Dimensions and Their Relationships With Work-Related Outcomes. (October 2019) - Andela, Marie; van der Doef, Margot
Our aim was to better understand the relationship between person–environment fit (PE fit) and several work-related outcomes, that is, burnout, job satisfaction, and turnover intention. To achieve this goal, direct effects of PE fit on these variables were explored as well as the indirect effects of PE fit on turnover intention through burnout and job satisfaction. The study was conducted on an occupationally heterogenous sample of 571 employees in France. Four types of fit were taken into account (person–job fit [PJ fit], person–organization fit [PO fit], person–group fit [PG fit], and person–supervisor fit [PS fit]). Correlations, regression, and mediation analyses were performed. Results indicated that the four dimensions of PE fit were positively related to job satisfaction and negatively associated with burnout and turnover intention. PJ fit and PO fit were more strongly correlated with these three work-related outcomes than PG fit and PS fit. Mediation analyses indicated that job satisfaction fully mediated the relationship between PJ fit, PO fit, PS fit, and turnover intention, while burnout partially mediated these relationships.